Research skills development in higher education students - Tiziana Priede Bergamini; Cristina López-Cózar Navarro (Laureate Education Inc, 2014)
This case study presents the development of a research project in a third-year undergraduate course, Family Business Administration. The research project aimed at promoting research skills in students. The authors formed working groups of no more than six students, and each group had to select an original research topic after conducting a literature review. Students were guided by the teachers and provided with initial reading materials, as well as an activity rubric specifying the minimum requirements of a scientific paper. The activity evaluation consisted of two parts, a written article (group assessment) and an oral presentation (individual assessment). After the activity concluded, students were asked to answer an online satisfaction survey. Results showed students viewed the activity as positive and appreciated the chance to develop several competencies, including research skills. The authors conclude several objectives were achieved, including: familiarize students with scientific research; make sure students are cable of finding information through primary sources; have students apply the knowledge acquired during the course; promote responsibility in students; cultivate in students the capacity to summarize ideas and expose them in a reasoned way; have students learn from the experiences and knowledge of others; and develop in students the capacity to synthesize all that information. -------------------------- El desarrollo de la capacidad investigadora en estudiantes de educación superior Resumen  Este estudio de caso presenta el desarrollo de un proyecto de investigación en la asignatura "Administración de la Empresa Familiar" de tercer curso. El proyecto de investigación tenía como propósito fomentar de forma específica la capacidad investigadora de los alumnos. Se formaron grupos de trabajo de no más de seis estudiantes, y cada grupo tenía que seleccionar un tema de investigación original tras realizar una búsqueda de literatura. Los docentes guiaron a los estudiantes proveyendo materiales de lectura, así como una rúbrica especificando los requisitos mínimos de un trabajo de divulgación científica. La evaluación de la actividad consistió de dos partes, un trabajo escrito (evaluado en grupo) y una presentación oral (evaluada individualmente). Una vez concluida la actividad, se les pidió a los estudiantes que respondieran una encuesta de satisfacción en línea. Los resultados mostraron que los estudiantes valoraron positivamente la experiencia y apreciaron la oportunidad de desarrollar varias competencias, incluyendo la capacidad investigadora. Las autoras determinaron que se alcanzaron varios objetivos, incluyendo: que los alumnos se familiaricen con la investigación científica, que sean capaces de buscar información en fuentes primarias, que apliquen los conocimientos adquiridos, que sean responsables, capaces de establecer objetivos y planificar el trabajo necesario para alcanzarlos, que sean capaces de resumir ideas y exponerlas de forma argumentada, que aprendan de las experiencias y conocimientos de otros y sean capaces de sintetizar toda esa información. DOI: 10.18870/hlrc.v4i1.194 PDF document contains both the original in Spanish and an English translation.